Nanoengineered biomimetic Cu-based nanoparticles for multifunational and efficient tumor treatment. (September 2021) - Chen, Zengzhen; Wu, Qiong; Guo, Wenna; Niu, Meng; Tan, Longfei; Wen, Ning; Zhao, Lisheng; Fu, Changhui; Yu, Jie; Ren, Xiangling; Liang, Ping; Meng, Xianwei
Abstract: The microwave dynamic therapy (MDT) mediated by cytotoxic reactive oxygen species (ROS) is a promising anticancer therapeutic method. However, the therapeutic efficiency of MDT is restricted by several limitations including insufficient ROS generation, strong proangiogenic response, and low tumor-targeting efficiency. Herein, we find that Cu-based nanoparticles can produce oxygen under microwave (MW) irradiation to raise the generation of ROS, such as O2, OH and 1 O2, especially O2 . On this basis, a nanoengineered biomimetic strategy is designed to improve the efficiency of MDT. After intravenous administration, the nanoparticles accumulate to the tumor site through targeting effect mediated by biomimetic modification, and it can continuously produce oxygen to raise the levels of ROS in tumor microenvironment under MW irradiation for MDT. Additionally, Apatinib is incorporated as antiangiogenic drug to downregulate the expression of vascular endothelial growth factor (VEGF), which can effectively inhibit the tumor angiogenesis after MDT. Hence, the tumor inhibition rate is as high as 96.79%. This study provides emerging strategies to develop multifunctional nanosystems for efficient tumor therapy by MDT.